The use of Career Growth Scale in Chinese nurses: Validity and reliability - Jingying Liu; Jipeng Yang; Yanhui Liu; Yang Yang; Hongfu Zhang (Elsevier, 2015)
Purpose: To test the validity and reliability of a modified Career Growth Scale (CGS) to assess nurse career growth. Method: A cross-sectional design was used to analyze the use of the CGS to survey 600 full-time registered nurses from Grade A hospitals in Tianjin. Results: A modified scale we called Career Growth of Nurse Scale (CGNS) is acceptable, valid, and reliable for the evaluation of nurse career growth in Chinese hospitals. This scale measured three main factors (career goal, career capacity, and career opportunity) and showed that nurse career growth differed across age, work seniority, and professional title. Conclusions: A three-dimensional scale of nurse career growth was presented. The results revealed CGNS has good validity and reliability.